UTILIZING SIMULATION TO ADVANCE PROGRAMMING PROFICIENCY AMONG COMPUTER ENGINEERING STUDENTS IN ANAMBRA STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the effectiveness of simulation-based learning in enhancing programming proficiency among computer engineering students in Anambra State, Nigeria. A quasi-experimental design was employed, involving 120 students from two universities, divided into an experimental group (using simulation) and a control group (using traditional methods). The objective was to assess whether simulation improves programming skills, problem-solving abilities, and retention compared to conventional teaching. Pre- and post-tests were administered, and data were analyzed using t-tests. Results indicate that the experimental group outperformed the control group significantly in programming proficiency (p < .05). The findings suggest that simulation is a valuable tool for advancing programming education in resource-constrained settings like Anambra State. Implications include the need for integrating simulation tools into curricula to bridge skill gaps and enhance employability.